Å sette en dronning i scene. Fremstillinger av kroningsopptoget for Isabeau av Bayern i Grandes Chroniques de France, 1400-1500 - Bø, Ragnhild M. (Hikuin, 2017)
Staging a Queen. Representations of the Coronation of Isabeau of Bavaria in the Grandes Chroniques de France, c.1400-1500 By Ragnhild M. Bø In the pageant that took place when Isabeau of Bavaria was crowned as Queen of France in August 1389, she was not only staged as a spectator to various tableaux acted out in front of her, but also put on display herself as e.g. the Virgin and St Anne. The pageant is minutely described by her contemporary Jean Froissart in book IV of his four volumes entitled Grandes Chroniques de France. This pageant is the only one included in a text which is mostly known for its descriptions of battles fought between the English and the French and their various allies during the Hundred Years War (1337-1453), as well as commenting upon aristocratic and chivalric behaviour. In this article, I take performance as the act of staging a person, and I discuss which of the many sensorial images created by Froissart in his account of Queen Isabeau’s pageant were later deployed as iconographical motifs in illuminated copies of his text throughout the fifteenth century, also in copies made well after the Queen’s death.